Social Integration Through Conflict: Mechanisms and Challenges in Pluralist Democracies - Nicole Deitelhoff; Cord Schmelzle (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
Conflicts are not usually associated with social integration, but rather with threats to it. They appear as a~cause of social distance, alienation and division. However, the sociology of conflict maintains that conflicts are as much a~source of social integration and cohesion as they are of division. Modern democratic societies in particular have developed the ability to enable and maintain social integration by simultaneously promoting and containing conflict. To do so, they make use of three different mechanisms: the dilution and pluralisation of conflicts, their institutional embedding, and the adaptation and appropriation of the social order through conflict. The article introduces these mechanisms, outlines how they materialise in modern democracies and discusses three current developments that threaten the balance between the promotion and containment of conflict: polarisation, radicalisation and depoliticisation. – – Konflikte werden gewöhnlich nicht mit sozialer Integration in Verbindung gebracht, sondern eher mit ihrer Bedrohung. Sie erscheinen als Ursache sozialer Distanz, Entfremdung und Spaltung. Die Konfliktsoziologie hält dem jedoch entgegen, dass Konflikte sowohl eine Quelle der Vergesellschaftung und des sozialen Zusammenhalts als auch der Spaltung sind. Insbesondere moderne demokratische Gesellschaften haben die Fähigkeit entwickelt, soziale Integration dadurch zu ermöglichen und aufrechtzuerhalten, dass sie Konflikte gleichzeitig fördern und eindämmen. Dazu bedienen sie sich dreier unterschiedlicher Mechanismen: der Verdünnung und Pluralisierung von Konflikten, ihrer institutionellen Einbettung sowie der Anpassung und Aneignung der sozialen Ordnung durch Konflikte. Der Beitrag stellt diese Mechanismen vor, beschreibt, wie sie in modernen Demokratien zum Tragen kommen und diskutiert drei aktuelle Entwicklungen, die das Gleichgewicht zwischen der Förderung und Eindämmung von Konflikten gefährden: Polarisierung, Radikalisierung und Entpolitisierung.
Keywords: 300; Sociology of conflict; Polarization; Social cohesion; Democratic theory; Political theory; Konfliktsoziologie; Polarisierung; Gesellschaftlicher Zusammenhalt; Demokratietheorie; Politische Theorie